A psicologia e os saberes indígenas: arvorecimento de um campo em disputa na produção dos saberes psicológicos - Ferreira, Murilo Centrone (2024)
This work demarcates questions and provocations, goes through some important historical points about the arrival of psychology in Brazil and its paths, which consolidated it as a science and profession, going through the foundation of regional and federal psychology councils (Sistema Conselhos), the tensions academics in Brazil and Latin America, whose objective is to carry out an attentive and centered psychology in these territories until the formulation of recent technical notes and guidelines on indigenous issues in Psychology. Along this path, we will highlight the American and European legacies that still reveal themselves to be hegemonic in the composition of the theoretical framework of training in psychology, aligned with the civilizational perspective mediated by capitalism, which removes from Brazilian psychology the possible contributions of the indigenous population to new theoretical and methodological formulations. . Brazilian psychology, as a powerful field for embracing possible indigenous psychology, is faced with disputes of all kinds. The focus here is on how such power struggles manifest themselves in the academic field and, in this sense, we will shed light on fractions of what indigenous people are teaching about their worldviews, the constitution of the subject, forms of social organization, dimensions ethics, orality versus the written record, from the perspective of Good Living, from what reveals itself to be restrictive within scientific production and how indigenous philosophy undermines such structures